A passage to India [videorecording (Blu-Ray)] - Heyman, John, 1933-; Sands, Edward (Producer); Brabourne, John; Goodwin, Richard B., 1934-; Lean, David, 1908-1991; Ashcroft, Peggy, 1907-1991; Davis, Judy, 1956-; Fox, James, 1939-; Guinness, Alec, 1914-2000; Havers, Nigel, 1949-; Banerjee, Victor; Jarre, Maurice; et al. (Columbia Pictures : [Distributed by] Sony Pictures Home Entertainment, 2008)
Adela Quested is a plucky young woman who journeys from England with the free-spirited Mrs. Moore. Flouting convention, the two women accompany the handsome Dr. Azis on a tour of the mysterious Marabar Caves. But things turn ugly when Adela returns scratched and bloodied from the expedition. As British authorities urge her to press charges against Aziz, the line separating truth and fantasy begin to blur.